In a triangle \( ABC \) , \( \angle A \) is twice of \( \angle B \) and \( a, b \) and \( c \) are respective sides opposite to angles \( \angle A, \angle B \) and \( \angle C \). then prove that \( a^2 = b(b+c) \)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewestLet D be on BC such that AD bisects \(\angle A\). Then \(\triangle ABD\) is isoceles. Also, \(\triangle ADC\) is similar to \(\triangle BAC\) as all their corresponding interior angles are equal.

By angle bisector theorem CD=\(\frac {ab}{b+c}\). However, since \(\triangle ACD\) is similar to \(\triangle BCA\), \(\frac {a}{b}=\frac {b}{\frac {ab}{b+c}}=\frac {b+c}{a}\). Cross multiplying gives the result. – Joel Tan · 2 years, 10 months ago

Log in to reply

One of the proofs is this.. Does anyone have a simpler proof?

Let \( \angle A = 2x \) , \( \angle B = x \)

From Sine rule,

\( \frac{Sin A}{a} = \frac{Sin B}{b} \)

\( \implies \frac{Sin A}{Sin B} = \frac{a}{b} \)

\( \implies \frac{Sin 2x}{Sin x} = \frac{a}{b} \)

\( \implies \frac{2 Cos x Sin x}{Sin x} = \frac{a}{b} \)

\( \implies 2 Cos x = \frac{a}{b} \) ...(1)

From Cosine rule,

\( Cos A = \frac{b^2 + c^2 - a^2}{2bc} \) ...(2)

\( Cos B = Cos x = \frac{a^2 + c^2 - b^2}{2ac} \) ...(3)

Now, \( Cos A = Cos 2x = Cos^{2} x - Sin^{2} x \)

\( \implies (Cos 2x) + 1 \)

\( = [ Cos^{2} x - Sin^{2} ] + [ Cos^{2} x + Sin^{2} x ] = 2 Cos^{2} x \)

From (1), \( 2 Cos^{2} x = ( Cos 2x ) + 1 = \frac{b^2 + c^2 - a^2}{2bc} + 1 \)

\( = 2 Cos^{2} x = \frac{b^2 + c^2 - a^2 + 2bc}{2bc} \) ...(4)

Dividing (4) with (3),

\( \frac{2 Cos^{2} x}{Cos x} \)

\( = 2 Cos x = \frac{b^2 + c^2 - a^2 + 2bc}{a^2 + c^2 - b^2} \times \frac{2ac}{2bc} \)

\( = 2 Cos x = \frac{b^2 + c^2 - a^2 + 2bc}{a^2 + c^2 - b^2} \times \frac{a}{b} \)

From (1), \( 2 Cos x = \frac{a}{b} \)

\( \implies \frac{a}{b} = \frac{b^2 + c^2 - a^2 + 2bc}{a^2 + c^2 - b^2} \times \frac{a}{b} \)

\( \implies \frac{b^2 + c^2 - a^2 + 2bc}{a^2 + c^2 - b^2} = 1 \)

\( \implies a^2 + c^2 - b^2 = b^2 + c^2 - a^2 + 2bc \)

\( \implies 2a^2 = 2b^2 + 2bc \)

\( \implies a^2 = b^2 + bc \)

\( = \boxed{a^2 = b(b+c)} \) – Muzaffar Ahmed · 2 years, 10 months ago

Log in to reply

– Karthik Akondi · 2 years, 10 months ago

zaffar u are superLog in to reply

– Joel Tan · 2 years, 10 months ago

Nice use of trigonometry, although similar triangles would quicken the processLog in to reply